IMPLEMENTASI MODEL PEMBELAJARAN PJBL DALAM EKSPLORASI BUDAYA NUSANTARA MELALUI ORNAMENT BATIK UNTUK MENINGKATKAN KREATIFITAS SISWA SEKOLAH DASAR - Septi, Sam Wulan; Insanul Qisti Bariyah; Heri Maria Zulfiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The presence of art is a crucial element in human life, enabling the development of creativity, sense, and initiative. Art education, from elementary to secondary levels, plays a vital role in shaping students' aesthetic sensitivity, appreciation for beauty, and overall sensitivity. Ki Hajar Dewantara also emphasized the importance of art in forming a well-rounded personality in students. Arts, Culture, and Crafts (SBdP) is a mandatory part of the educational curriculum, with visual arts as one of its branches, teaching skills such as drawing, painting, and creating geometric shapes. The project-based learning (PjBL) model is implemented in this innovation, encouraging students to actively engage in designing, gathering information, and completing creative projects. PjBL, which is student-centered, allows them to work autonomously in constructing their learning, as well as developing problem-solving skills, teamwork, and creativity. This study aims to examine the impact of implementing the PjBL model on students' creativity in SBdP learning. This research is a descriptive qualitative study, employing a sampling method with a total of 19 students. Data collection techniques in this study include observation, interviews, written tests, and documentation. The results of this study indicate that the innovation in SBdP learning can integrate various subject contents, and the implementation of the PjBL model has been proven to enhance students' creativity. Keywords: batik ornaments, creativity, PjBL